Magnetic field-assisted single-point incremental forming with a magnet ball tool. Issue 1 (2021) - Buffa, Gianluca; Yamaguchi, Hitomi; Gucciardi, Marco; Pinard, Dylan; Fratini, Livan
Abstract: This paper describes magnetic field-assisted single-point incremental forming (M-SPIF) with a Nd-Fe-B magnet ball tool. In M-SPIF, the tool driven by magnetic force plastically deforms a sheet. The polarity of the magnet tool helps to make the magnetic force (i.e., forming force) more controllable. In creating a truncated cone, the direction of the magnetic force gradually points more outward as the process progresses, and material is forced outwards from the cone center, increasing thinning in M-SPIF, while the cone center remains undeformed in traditional SPIF. Moreover, M-SPIF creates less localized plastic strain than traditional SPIF while forming the desired geometry.